Unmet Need of Contraceptives among Eligible Couples of Urban Slum Dwellers in Dhaka - Nahar, Shamsun; Amin, Farhana (Ibrahim Medical College Journal, 2009)
This cross-sectional study was conducted on married women residing in urban slums of Kamrangirchar in Dhaka to determine the magnitude of unmet need for family planning. A total of 265 married women of reproductive age who were fecund and living with husband were the sample of the study. The mean age of the respondents was 26.8±6.7 years. A little above 14% of the women were in the age group of 15-19 years. Almost equal proportion of respondents and their husbands were found to be illiterate. Nearly one-tenth of the respondents have not had ever experienced pregnancy, while 23% experienced pregnancy once, 18.1% twice and 33.6% three-four times, 17% more than four times. Among the respondents, 51.3% were currently using a contraceptive method. Around 5% were pregnant, which was intended. Another 3% wanted to conceive. The rest 41.1% wanted to use a contraceptive but certain barriers did not allow them to use the same suggesting that their family planning need was unmet. This need included limiting (21.5%) and spacing (19.6%). Lactational amenorrhea, no specific reasons, side effect of past contraceptive use, lack of support from husband or other family members, lack of proper knowledge of contraceptive and difficulties in obtaining contraceptive supplies were the cited reasons. Unmet need of contraceptive is high despite an extensive family planning programme in Bangladesh. Mean age at marriage is still below the legal age and gender discrimination plays a vital role in this unmet need. Ibrahim Med. Coll. J. 2009; 3(1): 24-28 Key words: Unmet need, contraceptive, reasons of unmet need doi: 10.3329/imcj.v3i1.2916